2009
DOI: 10.1016/j.jnt.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Any Diophantine quintuple contains a regular Diophantine quadruple

Abstract: A set {a 1 , . . . ,a m } of m distinct positive integers is called a Diophantine m-tuple if a i a j + 1 is a perfect square for all i, j withIn this paper, we show that if {a, b, c, d, e} is a Diophantine quintuple with a < b < c < d < e, then d = d + .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Let us mention that recently Fujita [13] has proved the analogous result for D(1)-m-tuples. The main difference in our proof is that we consider the binary recurrence sequences more carefully, so we obtain significantly improved gap principles.…”
Section: Introductionmentioning
confidence: 69%
“…Let us mention that recently Fujita [13] has proved the analogous result for D(1)-m-tuples. The main difference in our proof is that we consider the binary recurrence sequences more carefully, so we obtain significantly improved gap principles.…”
Section: Introductionmentioning
confidence: 69%
“…It suffices to show that u 4 = v 4 and u 6 > v 4 . The latter immediately follows from Lemma 2.10 (1) in [12] and its proof, in view of…”
Section: The Fundamental Solutions Of the System Of Diophantine Equatmentioning
confidence: 75%
“…It is known that there does not exist a Diophantine sextuple and that there does not exist only finitely many Diophantine quintuples ( [8]). Recently, we ( [12]) showed that if {a, b, c, d, e} is a Diophantine quintuple with a < b < c < d < e, then d = d + (note that all the quadruples contained in the quintuple, other than {a, b, c, d}, are irregular; see Section 1 in [12]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All we have to do is to find the real numbers satisfying the assumptions in Lemma 3.2. Using formulas (24) and (25) in [12], we have…”
Section: Application Of a Modified Rickert's Resultsmentioning
confidence: 99%